Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jai.12804
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of streptococcal infection in Nile tilapia Oreochromis niloticus (Linnaeus, 1758) using filter-feeding bivalve mussel Pilsbryoconcha exilis (Lea, 1838)

Abstract: Since bivalve mussels are able to graze heavily on bacteria, in this paper it is hypothesized that when mussels are cultured with fish, the filtering efficiency of the mussels will keep the bacterial population below a certain threshold and thus assist in reducing the risk of bacterial disease outbreaks. The ability of the filter-feeding bivalve mussel Pilsbryoconcha exilis to control Streptococcus agalactiae was tested in a laboratory-scale tilapia culture system. Juvenile Nile tilapia (Oreochromis niloticus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The source of the hemorrhages throughout the body could be the hemolysin produced by the Aeromonas retrieved bacteria, which hemolyzes red blood cells (RBCs), in addition to the elastase enzyme, which significantly contributes to vascular injury because the blood arteries are primarily made up of elastic and collagenous fibers. The clinical symptoms seen in this study almost the same as those identified by previously ( Ahmed and Shoreit, 2001 ; El-Ashram, 2002 ; Pretto-Giordano et al , 2010 ; Yardimci and Aydin, 2011 ; Noor El-Deen et al , 2014 ; Soliman et al , 2014 ; Othman et al , 2015 ; Dar et al , 2016 ; Omar et al , 2016 ; Abd El-Tawab et al , 2017 ; El-Barbary, 2017 ; Laith et al , 2017 ; Osman et al , 2017 ; Pech et al , 2017 ; Saleh et al , 2017 ; Amrullah et al , 2018 ; Khalil and Emeash, 2018 ; Hamouda et al , 2019 ; Hassan et al , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…The source of the hemorrhages throughout the body could be the hemolysin produced by the Aeromonas retrieved bacteria, which hemolyzes red blood cells (RBCs), in addition to the elastase enzyme, which significantly contributes to vascular injury because the blood arteries are primarily made up of elastic and collagenous fibers. The clinical symptoms seen in this study almost the same as those identified by previously ( Ahmed and Shoreit, 2001 ; El-Ashram, 2002 ; Pretto-Giordano et al , 2010 ; Yardimci and Aydin, 2011 ; Noor El-Deen et al , 2014 ; Soliman et al , 2014 ; Othman et al , 2015 ; Dar et al , 2016 ; Omar et al , 2016 ; Abd El-Tawab et al , 2017 ; El-Barbary, 2017 ; Laith et al , 2017 ; Osman et al , 2017 ; Pech et al , 2017 ; Saleh et al , 2017 ; Amrullah et al , 2018 ; Khalil and Emeash, 2018 ; Hamouda et al , 2019 ; Hassan et al , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…; Othman et al. ). This filter feeding improves stream clarity and increases macroinvertebrate resources in the river (Vaughn ), which could potentially increase the recreational value of the river.…”
Section: Discussionmentioning
confidence: 97%
“…Trophic changes in the Szczecin Lagoon waters observed in the recent decades (Wolnomiejski & Witek, 2013), caused by increased intensity of agricultural production and nutrient migration to surface waters (Burzyńska, 2019), may result in future elimination of numerous species sensitive to increased levels of nitrogen and phosphorus compounds. Such changes in the environmental conditions especially affect mussels (Cope et al, 2008), which are one of the most endangered groups of animals (Lopes-Lima et al, 2017;Böhm et al, 2020) How significant for the aqueous environment the freshwater mussels are is shown by the fact that they highly support water purification by filtering off bacteria from the water column (Othman et al, 2015). The most common factors considered in the assessment of the mussel resources and planning of conservation works include the present state of the population or variability over short periods of time.…”
Section: Age and Growth Of Musselsmentioning
confidence: 99%